Non-coated rubber plug for azide and aztreonam medicines and preparation method of non-coated rubber plug
By using a combination of brominated butyl rubber, ethylene-vinyl alcohol copolymer, crude glass fiber and diethylene triamine modified thiourea in the pharmaceutical plug, the cleanliness and airtightness of the pharmaceutical plugs when using Achi and Azutun drugs is solved, and efficient, economical and safe preparation of the plug is achieved.
Patent Information
- Application Number
- CN202411647148.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
When using Achi and Azurainan medicines, existing pharmaceutical glue plugs are difficult to meet the requirements of high cleanliness and airtightness, and are complex in manufacturing and costly.
The uncovered rubber plug design was adopted, brominated butyl rubber and ethylene-vinyl alcohol copolymer were used as the main material, and a mixture of crude glass fibers and diethylene triamine modified thiourea was added to improve the strength of the rubber plug, gas barrier properties and interface bonding strength.
The high cleanliness, airtightness and stability of the glue plug are achieved, reducing manufacturing complexity and cost, while avoiding the use of coating materials, and improving the safety and service life of the glue plug.
Abstract
Description
Technical Field
[0001] The present application relates to a drug rubber plug, and more specifically, to a non-film-covered rubber plug for Azithromycin and Aztreonam drugs and a preparation method thereof. Background Art
[0002] Azithromycin is the abbreviation of azithromycin, a new generation of macrolide drugs with strong anti-mycoplasma infection effects. Aztreonam is a new type of monoamide ring β-lactam antibiotic with the characteristics of third-generation cephalosporins and fourth-generation penicillins. It is used for infections caused by sensitive Gram-negative bacteria, such as pneumonia, biliary tract infections, as well as bone and joint infections, urinary tract infections, and can also be used for sepsis. Azithromycin and aztreonam are widely used drugs. After medication, they are widely distributed in the body and have higher concentrations in the kidneys, lungs, skin and other parts. In order to avoid side effects, high requirements are placed on the cleanliness and airtightness of the rubber plug. During puncture, no debris can fall out to contaminate the drug and endanger patient safety.
[0003] In order to improve the cleanliness of medical rubber stoppers, fluorinated polymer films are coated on the stoppers to inhibit the migration of low molecular weight substances from the stoppers into the medicines. However, this significantly increases the cost of materials, manufacturing complexity and product scrap rate. How to provide a rubber stopper that is simple to manufacture, does not require coating, has significantly reduced extractables, does not shed debris, and has low air permeability is an urgent problem to be solved. Summary of the invention
[0004] In order to solve the problem of high cleanliness and sealing of drug plugs, the present application provides a non-filmed plug for Azithromycin and Aztreonam drugs and a preparation method thereof.
[0005] In the first aspect, the present application provides a non-filmed rubber plug for Azithromycin and Aztreonam drugs, comprising the following components in parts by weight: 90-100 parts of brominated butyl rubber, 70-80 parts of ethylene-vinyl alcohol copolymer, 7-10 parts of vulcanizer, 1-2 parts of activator, 5-10 parts of plasticizer, 0.5-1 parts of thiourea, and 25-40 parts of a mixture of coarsened glass fiber and diethylenetriamine-modified thiourea.
[0006] By adopting the above scheme, bromobutyl rubber is used as the base material of the rubber plug, which is beneficial to the stability of the rubber plug and the barrier property to gas and solvent. The internal structure of the rubber plug is good, and the side methyl groups in the molecular chain are densely arranged, which limits the diffusion of low molecules, has good air tightness and water tightness, and can form good protection for drugs. A certain amount of ethylene-vinyl alcohol copolymer, namely EVOH, is added to participate in vulcanization to further improve the blocking of gas. The molding effect of the rubber plug is further improved by adding a certain amount of activator and plasticizer. Glass fiber has high strength and good barrier properties, good biocompatibility and stability, and is suitable for medical rubber plugs. After roughening, it has more surface active groups, larger specific surface area, greater friction with the rubber plug, higher interface bonding force with the rubber plug matrix, better strengthening effect on the rubber plug, and more stable rubber plug. By modifying thiourea with diethylenetriamine, the promotion effect of thiourea is improved, and the obtained rubber plug has higher toughness after curing and is not easy to fall off after puncture. The roughened glass fiber and diethylenetriamine modified thiourea are premixed and added together, and the diethylenetriamine modified thiourea is uniformly attached to and filled on the surface of the roughened fiber. After the mixture is added to the rubber system, it has a certain promoting effect on the vulcanization of the rubber plug. The rubber vulcanization effect is good at the contact interface between the roughened glass fiber and the rubber plug system, which reduces the vulcanization time and avoids the under-vulcanization or insufficient vulcanization of the rubber on the rough surface of the roughened glass fiber. The contact interface between the roughened glass fiber and the rubber plug matrix is more tightly connected, the roughened glass fiber and the rubber matrix form a better material whole, and the roughened glass fiber is more evenly interspersed in the rubber plug to optimize the internal structure of the rubber plug. During the needle puncture process, the stress is transmitted through the interface, and the roughened glass fiber bears the main stress. The better internal structure hinders the diffusion of low molecules, the rubber plug is cleaner, the prepared rubber plug is not easy to produce debris, and the rubber plug has good air tightness.
[0007] In a specific embodiment, the mass ratio of the coarsened glass fiber to the diethylenetriamine-modified thiourea in the mixture is (4.5-5.5):1.
[0008] By adopting the above scheme, diethylenetriamine-modified thiourea is evenly and completely attached to the surface of the roughened glass fiber, and the vulcanization promotion effect and interpenetration effect on the rubber plug are suitable for the component composition of the rubber plug. The interface bonding strength between the roughened glass fiber and the inside of the rubber plug is high, and there is no gap on the interface. The obtained rubber plug is not prone to stress concentration and chipping after being subjected to external force.
[0009] In a specific embodiment, the preparation step of the roughened glass fiber includes: adding the glass fiber to a sodium hydroxide aqueous solution, stirring, filtering, and washing to obtain the roughened glass fiber.
[0010] By adopting the above scheme, the preparation steps are relatively simple, the strength loss of the prepared glass fiber is small, the specific surface area is large, the interface in contact with the rubber matrix is larger, and the connection is relatively firm.
[0011] In a specific embodiment, the average fiber diameter of the glass fiber is 15-22 μm, the average length is 80-130 μm, the mass concentration of the sodium hydroxide aqueous solution is 5-7 g / L, and the stirring time is 10-12 minutes.
[0012] By adopting the above scheme, the glass fiber can be evenly dispersed inside the rubber plug and form a good interpenetration to reinforce the rubber plug. The obtained glass fiber has low strength loss, large specific surface area and high surface roughness. By limiting the acid concentration and stirring time, the surface of the glass fiber is rougher, and diethylenetriamine is better adhered to. The vulcanization promotion effect at the interface between the coarsened glass fiber and the rubber plug matrix is good, and the interface connection strength is higher.
[0013] In a specific embodiment, the roughened glass fibers are modified with an epoxy silane coupling agent.
[0014] By adopting the above scheme, the coarsened glass fiber modified with the epoxy silane coupling agent has better compatibility with the rubber plug system, higher adhesion, better rubber plug reinforcement effect, and can produce certain cross-linking with diethylenetriamine, further improving the bonding strength between the coarsened glass fiber and the rubber plug system and the reinforcement effect of the coarsened glass fiber on the rubber plug.
[0015] In a specific embodiment, the viscosity of the diethylenetriamine-modified thiourea is 270-300 mPa×s.
[0016] By adopting the above scheme, at this viscosity, diethylenetriamine modified thiourea can fully disperse, contact and wet the epoxy modified roughened glass fiber, and can maintain a certain degree of adhesion after being added to the rubber system. At the same time, the bonding strength of the two components after crosslinking and vulcanization is higher than the cohesive energy of the rubber plug. After the needle is inserted into the rubber plug, the stress can be better transmitted and it is not easy to fall off or break.
[0017] In a specific embodiment, the preparation steps of diethylenetriamine modified thiourea include: mixing diethylenetriamine and thiourea, heating for reaction, keeping the temperature, and cooling to obtain diethylenetriamine modified thiourea.
[0018] By adopting the above scheme, the preparation method is relatively simple, the yield is high, the by-products generated are less, the prepared rubber plug has high cleanliness, is not easy to produce small molecule impurities to contaminate the medicine, has a good effect on promoting vulcanization, the vulcanization degree inside the rubber plug is uniform, and there is no under-vulcanization and scorching.
[0019] In a specific embodiment, the heating reaction temperature is 90-110° C. and the insulation time is 0.5-1 hour.
[0020] By adopting the above scheme, the reaction temperature and the insulation time are limited, and the viscosity of the obtained diethylenetriamine modified thiourea is appropriate, which can fully wet and adhere to the coarsened glass fiber, thereby improving the reinforcing effect of the coarsened glass fiber on the plug system.
[0021] In a specific embodiment, the epoxy-modified roughened glass fibers are premixed with diethylenetriamine-modified thiourea.
[0022] In a second aspect, the present application provides a method for preparing a non-filmed rubber plug for Azithromycin and Aztreonam drugs, comprising the following steps: S1: Mixing: Mix all components in proportion and perform internal and open mixing to obtain a mixed rubber; S2: Preforming: Extrude the mixed rubber, perform calendaring, cooling and cut into pieces; S3: Vulcanization: Vulcanize the mixed rubber after cutting obtained in S2; S4: Molding: Punch the vulcanized mixed rubber in S3 to obtain a rubber plug; S5: Cleaning and drying: Use pure water to clean the rubber plug in S4 and then dry it.
[0023] By adopting the above technical scheme, the preparation process of the non-filmed rubber plug for the drugs of Azithromycin and Aztreonam is simple, and the quality of the prepared rubber plug is stable.
[0024] In a specific embodiment, the internal mixing in S1 is performed at 110-140°C for 4-6 minutes, the open mixing in S1 is performed at 100-110°C for 3-4 minutes, and the vulcanization temperature is 175-185°C.
[0025] By adopting the above scheme, the vulcanization time of the rubber plug is short, the vulcanization temperature is suitable for the component setting of the rubber plug of the present application, the internal vulcanization of the prepared rubber plug is uniform and sufficient, the vulcanization effect is good, and it performs well in the chip falling and air permeability experiments.
[0026] In summary, this application has the following beneficial effects: 1. The present application uses brominated butyl rubber and ethylene-vinyl alcohol copolymer in combination to prepare a rubber plug having high strength and gas barrier properties. By adding a certain amount of roughened glass fiber and a mixture of diethylenetriamine-modified thiourea, especially a mixture of epoxy-modified roughened glass fiber and diethylenetriamine-modified thiourea, to the rubber plug, crosslinking and vulcanization are promoted to jointly improve the interface bonding strength of the roughened glass fiber and the rubber plug system, the roughened glass fiber has a good reinforcing effect on the rubber plug, and the stress is better conducted by the roughened glass fiber, and it is not easy to fall off.
[0027] 2. The present application limits the mass ratio of the roughened glass fiber and the diethylenetriamine-modified thiourea, the size of the glass fiber and the concentration of the acid solution, the viscosity of the diethylenetriamine-modified thiourea, etc., so that the diethylenetriamine-modified thiourea can fully infiltrate the surface of the roughened glass fiber, further improve the interfacial bonding strength between the roughened glass fiber and the rubber plug system, and enhance the reinforcing effect of the roughened glass fiber on the rubber plug. DETAILED DESCRIPTION
[0028] To further help understand the technical solution of the present invention, several specific embodiments are provided to describe the technical solution of the present invention in more detail. All the embodiments described are only partial embodiments of the present invention, not all of them; the embodiments can be combined with each other, and the same or similar concepts or processes may not be described in detail in some embodiments. The following embodiments are further explanations of the present invention, and the present invention is not limited thereto.
[0029] The other experimental reagents, unless otherwise specified, were conventional commercial brands or obtained through conventional preparation processes.
[0030] Preparation Example Preparation Example 1: Roughened Glass Fiber 200 g of glass fiber was added to 1000 ml of 6 g / L sodium hydroxide aqueous solution, stirred at 25° C. for 10 minutes, filtered, and washed with deionized water for 4 times to obtain roughened glass fiber.
[0031] The glass fibers of this preparation example had an average diameter of 20 μm and an average length of 120 μm.
[0032] Preparation Example 2: Roughened Glass Fiber The only difference between the roughened glass fibers of this embodiment and those of the preparation example is that the average diameter of the glass fibers is 10 μm, the average length is 3 mm, and the mass concentration of the sodium hydroxide aqueous solution is 10 g / L.
[0033] Preparation Example 3: Epoxysilane Coupling Agent Modified Roughened Glass Fiber 200 g of the roughened glass fiber obtained in Preparation Example 1 and 150 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent KH-560 were added to 1000 ml of 30 vt% ethanol aqueous solution, heated at 80° C. for 1 hour, filtered, washed with pure water 3 times, and dried to obtain epoxysilane coupling agent modified roughened glass fiber.
[0034] Preparation Example 4: Vinyl silane coupling agent modified roughened glass fiber 200 g of the roughened glass fiber obtained in Preparation Example 1 and 150 g of vinyltrimethoxysilane coupling agent A-171 were added to 1000 ml of 30 vt% ethanol aqueous solution, heated at 80° C. for 1 hour, filtered, washed with pure water 3 times, and dried to obtain vinylsilane coupling agent modified roughened glass fiber.
[0035] Preparation Example 5: Diethylenetriamine modified thiourea: 100g of diethylenetriamine and 40g of thiourea were mixed, stirred evenly, heated to 90°C for reaction, cooled to 50°C after 1 hour, stirred continuously and kept warm for 1 hour, cooled to room temperature, and diethylenetriamine modified thiourea was obtained. The viscosity of the diethylenetriamine modified thiourea obtained in this preparation example was 274.1mPa×s.
[0036] Preparation Example 6: Diethylenetriamine modified thiourea: 100g of diethylenetriamine and 40g of thiourea were mixed, stirred evenly, heated to 110°C for reaction, cooled to 50°C after 1 hour, stirred continuously and kept warm for 1 hour, cooled to room temperature, and diethylenetriamine modified thiourea was obtained. The viscosity of the diethylenetriamine modified thiourea obtained in this preparation example was 296.4mPa×s.
[0037] Preparation Example 7: Diethylenetriamine modified thiourea: 100g of diethylenetriamine and 40g of thiourea were mixed, stirred evenly, heated to 70°C for reaction, cooled to 50°C after 1 hour, stirred continuously and kept warm for 1 hour, cooled to room temperature, and diethylenetriamine modified thiourea was obtained. The viscosity of the diethylenetriamine modified thiourea obtained in this preparation example was 244.7mPa×s.
[0038] Preparation Example 8: Mixture Preparation: 200 g of the roughened glass fiber obtained in Preparation Example 1 and 70 g of the diethylenetriamine-modified thiourea obtained in Preparation Example 5 were uniformly mixed to obtain a mixture.
[0039] Preparation Example 9: Mixture Preparation: 200 g of the roughened glass fiber obtained in Preparation Example 2 and 70 g of the diethylenetriamine-modified thiourea obtained in Preparation Example 5 were uniformly mixed to obtain a mixture.
[0040] Preparation Example 10: Mixture Preparation: 200 g of the epoxy silane coupling agent modified roughened glass fiber prepared in Preparation Example 3 and 70 g of the diethylenetriamine modified thiourea prepared in Preparation Example 5 were mixed uniformly to obtain a mixture.
[0041] Preparation Example 11: Mixture Preparation: 200 g of the vinyl silane coupling agent modified roughened glass fiber prepared in Preparation Example 4 and 70 g of the diethylenetriamine modified thiourea prepared in Preparation Example 5 were mixed uniformly to obtain a mixture.
[0042] Preparation Example 12: Mixture Preparation: 350 g of the roughened glass fiber obtained in Preparation Example 1 and 50 g of the diethylenetriamine-modified thiourea obtained in Preparation Example 5 were uniformly mixed to obtain a mixture.
[0043] Preparation Example 13: Mixture Preparation: 270 g of the roughened glass fiber obtained in Preparation Example 1 and 60 g of the diethylenetriamine-modified thiourea obtained in Preparation Example 5 were uniformly mixed to obtain a mixture.
[0044] Preparation Example 14: Mixture Preparation: 270 g of the roughened glass fiber obtained in Preparation Example 1 and 60 g of the diethylenetriamine-modified thiourea obtained in Preparation Example 6 were uniformly mixed to obtain a mixture.
[0045] Preparation Example 15: Mixture Preparation: 270 g of the roughened glass fiber obtained in Preparation Example 1 and 60 g of the diethylenetriamine-modified thiourea obtained in Preparation Example 7 were uniformly mixed to obtain a mixture. Example
[0046] Example 1 This example includes the following raw materials: 900 g of brominated butyl rubber, 700 g of ethylene-vinyl alcohol copolymer, 100 g of sulfur, 20 g of magnesium oxide, 100 g of paraffin wax, 10 g of thiourea, and 250 g of a mixture of coarsened glass fiber obtained in Preparation Example 8 and diethylenetriamine-modified thiourea.
[0047] The preparation process is as follows: S1: Mixing: Mix all components evenly according to the proportion, perform internal mixing at 120°C for 5 minutes and open mixing at 120°C for 5 minutes to obtain a mixed rubber; S2: Preforming: Extrude the mixed rubber, calender, cool and cut into pieces; S3: Vulcanization: Vulcanize the mixed rubber cut into pieces obtained in S2 by injection vulcanization molding process at 180°C and 220 bar, and the injection tube temperature is 70°C; S4: Molding: Punch the vulcanized mixed rubber in S3 to obtain a rubber plug; S5: Cleaning and drying: Use pure water to clean the rubber plug in S4, and then dry it with hot air at 50°C.
[0048] Example 2 This example includes the following raw materials: 1000 g of brominated butyl rubber, 800 g of ethylene-vinyl alcohol copolymer, 70 g of sulfur, 10 g of magnesium oxide, 50 g of paraffin wax, 5 g of thiourea, and 400 g of a mixture of coarsened glass fiber obtained in Preparation Example 8 and diethylenetriamine-modified thiourea.
[0049] The preparation process is as follows: S1: Mixing: Mix all components evenly according to the proportion, perform internal mixing at 120°C for 5 minutes and open mixing at 120°C for 5 minutes to obtain a mixed rubber; S2: Preforming: Extrude the mixed rubber, calender, cool and cut into pieces; S3: Vulcanization: Vulcanize the mixed rubber cut into pieces obtained in S2 by injection vulcanization molding process at 180°C and 220 bar, and the injection tube temperature is 70°C; S4: Molding: Punch the vulcanized mixed rubber in S3 to obtain a rubber plug; S5: Cleaning and drying: Use pure water to clean the rubber plug in S4, and then dry it with hot air at 50°C.
[0050] Example 3 This example includes the following raw materials: 950 g of brominated butyl rubber, 750 g of ethylene-vinyl alcohol copolymer, 85 g of sulfur, 15 g of magnesium oxide, 75 g of paraffin wax, 8 g of thiourea, and 320 g of a mixture of coarsened glass fiber obtained in Preparation Example 8 and diethylenetriamine-modified thiourea.
[0051] The preparation process is as follows: S1: Mixing: Mix all components evenly according to the proportion, perform internal mixing at 120°C for 5 minutes and open mixing at 120°C for 5 minutes to obtain a mixed rubber; S2: Preforming: Extrude the mixed rubber, calender, cool and cut into pieces; S3: Vulcanization: Vulcanize the mixed rubber cut into pieces obtained in S2 by injection vulcanization molding process at 180°C and 220 bar, and the injection tube temperature is 70°C; S4: Molding: Punch the vulcanized mixed rubber in S3 to obtain a rubber plug; S5: Cleaning and drying: Use pure water to clean the rubber plug in S4, and then dry it with hot air at 50°C.
[0052] Embodiment 4: The difference between this embodiment and embodiment 3 is only that: This example includes the following raw materials: 950 g of brominated butyl rubber, 750 g of ethylene-vinyl alcohol copolymer, 85 g of sulfur, 15 g of magnesium oxide, 75 g of paraffin wax, 8 g of thiourea, and 320 g of the mixture obtained in Preparation Example 9.
[0053] Embodiment 5: The difference between this embodiment and embodiment 3 is only that: This example includes the following raw materials: 950 g of brominated butyl rubber, 750 g of ethylene-vinyl alcohol copolymer, 85 g of sulfur, 15 g of magnesium oxide, 75 g of paraffin wax, 8 g of thiourea, and 320 g of the mixture obtained in Preparation Example 10.
[0054] Embodiment 6: The difference between this embodiment and embodiment 3 is only that: This example includes the following raw materials: 950 g of brominated butyl rubber, 750 g of ethylene-vinyl alcohol copolymer, 85 g of sulfur, 15 g of magnesium oxide, 75 g of paraffin wax, 8 g of thiourea, and 320 g of the mixture obtained in Preparation Example 11.
[0055] Embodiment 7: The difference between this embodiment and embodiment 5 is only that: This example includes the following raw materials: 950 g of brominated butyl rubber, 750 g of ethylene-vinyl alcohol copolymer, 85 g of sulfur, 15 g of magnesium oxide, 75 g of paraffin wax, 8 g of thiourea, and 320 g of the mixture obtained in Preparation Example 12.
[0056] Embodiment 8: The difference between this embodiment and embodiment 5 is only that: This example includes the following raw materials: 950 g of brominated butyl rubber, 750 g of ethylene-vinyl alcohol copolymer, 85 g of sulfur, 15 g of magnesium oxide, 75 g of paraffin wax, 8 g of thiourea, and 320 g of the mixture obtained in Preparation Example 13.
[0057] Embodiment 9: The difference between this embodiment and embodiment 5 is only that: This example includes the following raw materials: 950 g of brominated butyl rubber, 750 g of ethylene-vinyl alcohol copolymer, 85 g of sulfur, 15 g of magnesium oxide, 75 g of paraffin wax, 8 g of thiourea, and 320 g of the mixture obtained in Preparation Example 14.
[0058] Embodiment 10: The difference between this embodiment and embodiment 5 is only that: This example includes the following raw materials: 950 g of brominated butyl rubber, 750 g of ethylene-vinyl alcohol copolymer, 85 g of sulfur, 15 g of magnesium oxide, 75 g of paraffin wax, 8 g of thiourea, and 320 g of the mixture obtained in Preparation Example 15.
[0059] Embodiment 11: The difference between this embodiment and embodiment 3 is only that: The preparation process is as follows: S1: Mixing: Mix all components evenly according to the proportion, and perform internal mixing at 110°C for 5 minutes and open mixing at 140°C for 5 minutes to obtain a mixed rubber; S2: Preforming: Extrude the mixed rubber, calender, cool and cut into pieces; S3: Vulcanization: Vulcanize the mixed rubber cut into pieces obtained in S2 by injection vulcanization molding process at 195°C and 220 bar, and the injection tube temperature is 70°C; S4: Molding: Punch the vulcanized mixed rubber in S3 to obtain a rubber plug; S5: Cleaning and drying: Use pure water to clean the rubber plug in S4, and then dry it with hot air at 50°C.
[0060] Comparative Example Comparative Example 1 This comparative example includes the following raw materials: 950 g of brominated butyl rubber, 750 g of ethylene-vinyl alcohol copolymer, 85 g of sulfur, 15 g of magnesium oxide, 75 g of paraffin wax, 8 g of thiourea, and 320 g of the roughened glass fiber obtained in Preparation Example 1.
[0061] The preparation process is as follows: S1: Mixing: Mix all components evenly according to the proportion, perform internal mixing at 120°C for 5 minutes and open mixing at 120°C for 5 minutes to obtain a mixed rubber; S2: Preforming: Extrude the mixed rubber, calender, cool and cut into pieces; S3: Vulcanization: Vulcanize the mixed rubber cut into pieces obtained in S2 by injection vulcanization molding process at 180°C and 220 bar, and the injection tube temperature is 70°C; S4: Molding: Punch the vulcanized mixed rubber in S3 to obtain a rubber plug; S5: Cleaning and drying: Use pure water to clean the rubber plug in S4, and then dry it with hot air at 50°C.
[0062] Comparative Example 2 This comparative example includes the following raw materials: 950 g of brominated butyl rubber, 750 g of ethylene-vinyl alcohol copolymer, 85 g of sulfur, 15 g of magnesium oxide, 75 g of paraffin wax, 8 g of thiourea, and 200 g of a mixture of coarsened glass fiber obtained in Preparation Example 8 and diethylenetriamine-modified thiourea.
[0063] The preparation process is as follows: S1: Mixing: Mix all components evenly according to the proportion, perform internal mixing at 120°C for 5 minutes and open mixing at 120°C for 5 minutes to obtain a mixed rubber; S2: Preforming: Extrude the mixed rubber, calender, cool and cut into pieces; S3: Vulcanization: Vulcanize the mixed rubber cut into pieces obtained in S2 by injection vulcanization molding process at 180°C and 220 bar, and the injection tube temperature is 70°C; S4: Molding: Punch the vulcanized mixed rubber in S3 to obtain a rubber plug; S5: Cleaning and drying: Use pure water to clean the rubber plug in S4, and then dry it with hot air at 50°C.
[0064] Performance test test 1: Referring to the standard YBB 00042005-2015 halogenated butyl rubber stopper for injection, the puncture and chipping of the rubber stoppers prepared in the embodiment and the comparative example were tested, and the test results are summarized in Table 1; Test 2: The air tightness of the rubber plugs prepared in the examples and comparative examples was tested with reference to the standard GB / T 7755-2003. The test results are summarized in Table 1.
[0065] Table 1 Puncture debris <![CDATA[Air permeability (*10 17 m 2 / Pa*s)]]> Example 1 1 1.6 Example 2 1 1.7 Example 3 1 1.6 Example 4 2 2.0 Example 5 0 1.4 Example 6 2 1.5 Example 7 1 1.4 Example 8 0 1.0 Example 9 0 1.1 Example 10 2 2.1 Embodiment 11 4 2.0 Comparative Example 1 8 4.4 Comparative Example 2 5 2.4 In combination with Examples 1-3, Comparative Examples 1-2 and referring to Table 1, the present application strengthens the rubber plug by adding a certain mass of roughened glass fiber and a diethylenetriamine modified thiourea mixture into brominated butyl rubber and ethylene-vinyl alcohol copolymer, optimizes the interface connection between the roughened glass fiber and the rubber plug matrix, disperses the stress, and obtains a rubber plug with less puncture debris and good air tightness.
[0066] In combination with Examples 3-6 and referring to Table 1, the present application further optimizes the interface connection between the roughened glass fiber and the plug matrix by further limiting the roughened glass fiber to be the roughened glass fiber modified by the epoxy silane coupling agent.
[0067] In combination with Examples 5, 7-8 and referring to Table 1, the present application further optimizes the interface connection between the roughened glass fiber and the plug matrix by limiting the mass ratio of the roughened glass fiber and the diethylenetriamine-modified thiourea.
[0068] In combination with Examples 8-10 and referring to Table 1, the present application adjusts the viscosity of the diethylenetriamine-modified thiourea by adjusting the process parameters in the preparation process, so that it can fully infiltrate and adhere to the surface of the epoxy silane coupling agent-modified roughened glass fiber, and will not cause insufficient infiltration and too thick an adhesion layer due to high viscosity, nor will it cause too little adhesion due to too low viscosity. The interface connection strength between the epoxy silane coupling agent-modified roughened glass fiber and the plug matrix inside the prepared rubber plug is high, the glass fiber has a good reinforcing effect on the rubber plug, it is not easy to fall off during the penetration test, and the air permeability is low.
[0069] In combination with Examples 3 and 11 and referring to Table 1, the present application limits the process parameters of the preparation process, slightly reduces the temperature and time of the vulcanization process, which is suitable for the plug components of the present application. The internal vulcanization of the prepared plug is uniform and sufficient, the coarsened glass fiber is well combined with the plug system, and the performance of the plug is better enhanced.
[0070] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A non-filmed rubber plug for Azithromycin and Aztreonam drugs, characterized in that: The non-filmed rubber plug for Azithromycin and Aztreonam drugs comprises the following raw materials in parts by weight: 90-100 parts of brominated butyl rubber, 70-80 parts of ethylene-vinyl alcohol copolymer, 7-10 parts of vulcanizer, 1-2 parts of activator, 5-10 parts of plasticizer, 0.5-1 parts of thiourea, and 25-40 parts of a mixture of coarsened glass fiber and diethylenetriamine-modified thiourea.
2. The non-film-covered rubber plug for Azithromycin and Aztreonam medicines according to claim 1, characterized in that: The mass ratio of the coarsened glass fiber to the diethylenetriamine modified thiourea in the mixture is (4.5-5.5):
1.
3. The non-filmed rubber plug for Azithromycin and Aztreonam medicines according to claim 1, characterized in that: The preparation steps of the roughened glass fiber include: adding the glass fiber into a sodium hydroxide aqueous solution, stirring, filtering, and washing to obtain the roughened glass fiber.
4. The non-filmed rubber plug for Azithromycin and Aztreonam medicines according to claim 3, characterized in that: The average fiber diameter of the glass fiber is 15-22 μm, the average length is 80-130 μm, the mass concentration of the sodium hydroxide aqueous solution is 5-7 g / L, and the stirring time is 10-12 minutes.
5. The non-filmed rubber plug for Azithromycin and Aztreonam medicines according to claim 1, characterized in that: The roughened glass fiber is modified by an epoxy silane coupling agent.
6. The non-film-covered rubber plug for Azithromycin and Aztreonam medicines according to claim 4, characterized in that: The viscosity of the diethylenetriamine modified thiourea is 270-300 mPa×s.
7. The non-filmed rubber plug for Azithromycin and Aztreonam medicines according to claim 1, characterized in that: The preparation steps of the diethylenetriamine modified thiourea include: mixing diethylenetriamine and thiourea, heating for reaction, heat preservation, and cooling to obtain the diethylenetriamine modified thiourea.
8. The non-film-covered rubber plug for Azithromycin and Aztreonam medicines according to claim 7, characterized in that: The heating reaction temperature is 90-110° C., and the insulation time is 0.5-1 hour.
9. A method for preparing a non-filmed rubber plug for Azithromycin and Aztreonam medicines according to any one of claims 1 to 8, characterized in that: Preparation method The following steps are involved: S1: Mixing: Mix all components according to the proportion and perform internal and external mixing to obtain a mixed rubber; S2: Preforming: Extrude the mixed rubber, calender, cool and cut into pieces; S3: Vulcanization: Vulcanize the mixed rubber after cutting obtained in S2; S4: Molding: Punch the vulcanized mixed rubber in S3 to obtain a rubber plug; S5: Cleaning and drying: Use pure water to clean the rubber plug in S4 and then dry it.
10. The method for preparing a non-filmed rubber plug for Azithromycin and Aztreonam medicines according to claim 9, characterized in that: The internal mixing in S1 is carried out at 110-140°C for 4-6 minutes, the open mixing in S1 is carried out at 100-110°C for 3-4 minutes, and the vulcanization temperature is 175-185°C.
Citation Information
Patent Citations
Thiourea modified low temperature curing agent and preparation method thereof
CN102604044A
Epoxy resin solvent-free low temperature curing agent, preparation method and application thereof
CN103980463A
Quartz special material and preparation method thereof
CN115584228A
Medical low-permeability pre-pouring rubber plug and preparation method thereof
CN117264336A
Rubber bottle cap for surface film coated medicine
CN2441750Y